Proteomics of Colwellia psychrerythraea at subzero temperatures – a life with limited movement, flexible membranes and vital DNA repair. (5th February 2015) - Nunn, Brook L.; Slattery, Krystal V.; Cameron, Karen A.; Timmins‐Schiffman, Emma; Junge, Karen
Summary The mechanisms that allow psychrophilic bacteria to remain metabolically active at subzero temperatures result from form and function of their proteins. We present first proteomic evidence of physiological changes of the marine psychrophile Colwellia psychrerythraea 34H (Cp34H) after exposure to subzero temperatures (−1, and −10°C in ice) through 8 weeks. Protein abundance was compared between different treatments to understand the effects of temperature and time, independently and jointly, within cells transitioning to, and being maintained in ice. Parallel [3H]‐leucine and [3H]–thymidine incubations indicated active protein and DNA synthesis to −10°C. Mass spectrometry‐based proteomics identified 1763 proteins across four experimental treatments. Proteins involved in osmolyte regulation and polymer secretion were found constitutively present across all treatments, suggesting that they are required for metabolic success below 0°C. Differentially abundant protein groups indicated a reallocation of resources from DNA binding to DNA repair and from motility to chemo‐taxis and sensing. Changes to iron and nitrogen metabolism, cellular membrane structures, and protein synthesis and folding were also revealed. By elucidating vital strategies during life in ice, this study provides novel insight into the extensive molecular adaptations that occur in cold‐adapted marine organisms to sustain cellular function in their habitat.